Adenocarcinoma jejunum: A rare cause of acute onset vomiting (Indian Journal of Case Reports, 2020)
Small intestine malignancies are very rare and account for <5% of gastrointestinal malignancies. Of these, around 64% occur in the duodenum, 13% in the jejunum, and 13% in the ileum. They mostly present as non-specific symptoms due to which the diagnosis is often delayed. We present the case of a 57-year-old female who presented with a short vague history of pain abdomen and vomiting. The abdominal ultrasound was normal which further delayed the diagnosis. The computed tomography scan was done which revealed circumferential thickening of the jejunal wall. On histopathology, the final diagnosis of adenocarcinoma was made.